SOSIAL MEDIA STRATEGY OF NEW KPOP ALBUM : A VISUAL ANALYSIS OF BLACKPINK’S PHOTO TEASER - Kusumawati, Yudhistya Ayu; Widita, Anindya (UI Scholars Hub, 2021)
Manuscript type: Research article. Research Aims: This paper examined visual concept in Blackpink photo teaser as the promotion strategy in social media. Design/methodology/approach: This research was carried with qualitative approach, using Roland Barthes semiotics analysis to identify sign and symbol to identify visual meaning of Blackpink photo teaser and how the group is being presented through social media. Research Findings: Blackpink photo teasers have visual appeals which is consistent with the brand of the group. The girl crush and duality concepts of black and pink characters representing beautiful and strong persona were the message intended to be delivered through social media to the audience. Theoretical Contribution/Originality: This research explored the message contained within the visual concept in promotional photo teasers of a K-Pop group, Blackpink, as a social media strategy in promoting the new album. It is notable that the group wanted to project certain image through the photo teasers of the new album. Practitioner/Policy Implication: This research noted that the promotional strategy of a brand, in this case, the K-Pop group, in social media takes into consideration the brand identity and message appeals other than the visual aspect. Research limitation/Implications: This research only focused on one K-Pop group and a new album. Further research can be done covering multiple groups or multiple new albums to identify variety of concepts and strategies in social media.